Green Marketing and Environment - Sharma, Bed Nath (Janapriya Journal of Interdisciplinary Studies, 2018)
Green revolution is protecting our earth, people and many more through a natural phenomenon in everyday life. Green marketing is a tool used by many companies in various industries to follow this trend. There have been a lot of literature review on green marketing over the years, here analysis of the aspects of green marketing on customer value addition, satisfaction, environmental safety, sustainable development, benefits to stakeholders, prospects are presented. This can be used by researchers who need to study green marketing on these issues.